Distribution and minimum population size of Eurasian lynx (Lynx lynx) in Croatia in the period 2018–2020 : Rasprostranjenost i najmanja veličina populacije euroazijskog risa (Lynx lynx) u Hrvatskoj u razdoblju 2018.–2020 - Gomerčić, Tomislav (Array, 2021)
Scientific data on distribution and abundance of endangered species are the foundation for their effective conservation and management. In this paper, we present results of the first scientifically – based estimation of lynx population size in Croatia. The goal of the study was to determine the area of lynx distribution and to estimate the minimum size of lynx population in Croatia in the period 2018 - 2020. To determine lynx distribution, 902 signs of lynx presence were collected in the period from the beginning of May 2018 until the end of April 2020. Out of those, 92.8% of lynx observations were categorized as C1, 2.8% as C2 and 4.4% as C3. Permanent lynx presence was confirmed in Primorsko – Goranska and Ličko – Senjska county, in southern part of Karlovac county and north-eastern part of Zadar county on the total surface of 7200 km2. For the minimum population size estimation, 804 camera trap photographs led to identification of 89 – 108 adult lynxes. Among 108 identified individuals there were 29 females, 22 males, while for 7 animals the sex was not determined. During the two reproductive seasons, we photographed 44 cubs in 25 litters. Future important steps in lynx population monitoring are correcting the deficiencies identified in this study and implementation of methodology that will allow us to use spatial capture recapture models for estimation of lynx abundance in Croatia.